Examining Patient Safety Culture in Hospitals: A Systematic Review - Jendraatmaja, I Nengah Dwi; Pebriana, Indah; Apriliyanti, Putu Metha; Dewi, Fenny Virginia Sandra; Putra, Anggi Suswibudi; Putra, I Komang Pande Prajadhita Wibawa; Jibran, Lalu Bayazid (Jurnal Jaminan Kesehatan Nasional, 2025)
Patient Safety Culture (PSC) is critical in healthcare organizations, influencing patient outcomes and care quality. This study is a systematic review that provides a comprehensive understanding of PSC in hospitals by synthesizing the current literature using the PRISMA framework and focusing on identifying key components, determinants, and factors influencing healthcare professionals’ attitudes and perceptions toward PSC. A systematic search of the SCOPUS database identified 19,129 documents on PSC, of which 21 were included after rigorous screening and application of eligibility criteria. Key findings highlight the importance of effective leadership, communication, teamwork, and organizational learning in fostering a positive PSC. Supportive leadership and non-punitive environments encourage error reporting, whereas continuous professional development and stress-reduction programs enhance safety culture. Factors such as work-related stress, professional commitment, and organizational culture significantly impact PSC. Understanding these factors is essential for designing strategies to deal with healthcare professionals’ specific needs and challenges. This systematic review also reveals gaps in research on the causal relationships and mechanisms that shape PSC, suggesting that further studies are needed to develop more effective interventions. Practical implications emphasize the importance of leadership training, regular safety training sessions, stress reduction programs, and evidence-based practices. This review provides actionable insights for healthcare administrators, policymakers, and practitioners aiming to improve patient safety, offering a comprehensive understanding of PSC components and strategies for enhancement. This study contributes to efforts to create safer healthcare environments and improve patient outcomes by bridging the gap between theory and practice, underscoring the necessity of integrated, continuous approaches to PSC.